Efek Pemberian Edukasi Buklet dan Pendampingan Kader terhadap Konsumsi Tablet Tambah Darah pada Ibu Hamil Anemia di Jakarta Timur: Effect of Booklet Education and Cadre Assistance on Iron Tablets Consumption among Anemic Pregnant Women in East Jakarta - Fayasari, Adhila; Istianah, Isti; Fauziana, Sri (Universitas Airlangga, 2024)
Background: Anemia during pregnancy significantly increases maternal risk and poor pregnancy outcomes by 1.71-fold. Enhancing pregnant women's knowledge and adherence to health guidelines requires a comprehensive approach. Objectives: This study analyzed the effects of booklet education and cadre assistance on adherence to iron tablet consumption among anemic pregnant women in East Jakarta. Methods: This quasi-experimental study was conducted in 2019 on anemic pregnant women in Makasar Public Health Center, Jakarta. This study comprised three groups: iron-folic acid supplementation only (IF), iron-folic acid supplementation with booklet education (IFB), and iron-folic acid supplementation with booklet education and cadre assistance (IFBA), serving as control, intervention I, and intervention II, respectively. The interventions lasted for three months. Adherence to iron supplementation and knowledge, attitude, and behavior (KAB) regarding anemia were measured. The data were analyzed using ANOVA/Kruskall-Wallis test, Wilcoxon test, and Mc-Nemar test with a significance level of 0.05. Results: There was no difference in the increase of knowledge and behavior regarding anemia among the three groups (p < 0.05) although the behavior score in the IFBA group was significantly higher than in the other two groups. In addition, there was no difference in the percentage of adherence to iron tablet consumption before and after the intervention in the IF, IFB, and IFBA groups (p > 0.05). However, the IFBA group showed an increase of about 41% in adherence. Conclusions: There was no difference in the increase of knowledge and attitude regarding anemia among the three groups, except for behavior. However, the IFBA group showed a significant increase in knowledge, attitude, and behavior after the intervention.